2016
DOI: 10.1186/s40478-016-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

The identification of human pituitary adenoma-initiating cells

Abstract: Classified as benign central nervous system (CNS) tumors, pituitary adenomas account for 10% of diagnosed intracranial neoplasms. Although surgery is often curative, patients with invasive macroadenomas continue to experience significant morbidity and are prone to tumor recurrence. Given the identification of human brain tumor-initiating cells (TICs) that initiate and maintain tumor growth while promoting disease progression and relapse in multiple CNS tumors, we investigated whether TICs also drive the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
(87 reference statements)
2
24
0
Order By: Relevance
“…However, these cells were sensitive to the antiproliferative effect of drugs (in this case, dopamine/somatostatin chimeric agonists), which does not fit with the general concept of therapy resistance of TSC. In another recent study, CD15 + cells were identified in pituitary adenomas exhibiting higher sphere-forming capacity than the remaining cells, and upregulated expression of SOX2 (Manoranjan et al 2016). The latter finding is in agreement with an earlier report that showed SOX2 expression in a candidate TSC population as identified by SP efflux capacity (Mertens et al 2015).…”
Section: :3supporting
confidence: 81%
“…However, these cells were sensitive to the antiproliferative effect of drugs (in this case, dopamine/somatostatin chimeric agonists), which does not fit with the general concept of therapy resistance of TSC. In another recent study, CD15 + cells were identified in pituitary adenomas exhibiting higher sphere-forming capacity than the remaining cells, and upregulated expression of SOX2 (Manoranjan et al 2016). The latter finding is in agreement with an earlier report that showed SOX2 expression in a candidate TSC population as identified by SP efflux capacity (Mertens et al 2015).…”
Section: :3supporting
confidence: 81%
“…Similar results were obtained by the intracranial injection in nude mice of 10,000 CD133 + /nestin + PA cells, which gave rise to tumors, detectable after 6 weeks from the graft (83). In another study, one PASC culture from a null PA, sorted for CD15 expression, was pseudo-orthotopically injected in the brain of three mice (84). In agreement with the CSC theory, 50,000 CD15 + cells generated tumors when injected in the mouse brain, while up to 500,000 CD15 − cells were not tumorigenic.…”
Section: In Vivo Tumorigenic Abilitysupporting
confidence: 69%
“…Comparing the original tumor with the xenograft, both specimens were negative for GFAP, alphasmooth muscle actin, EMA, and TTF1, and, according to the neuroendocrine derivation, both expressed synaptophysin and CD56. Interestingly, desmin and myogenin were unexpectedly expressed only in the xenograft but not in the original PA, suggesting that CD15 + PASCs possess a microenvironmentdependent multi-lineage potential (84).…”
Section: In Vivo Tumorigenic Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that primary central nervous system tumors contain tumor-initiating cells (TICs) with tumorigenic properties that contribute to maintainence of tumor growth and promote disease progression. A recent report investigated whether TICs also contribute to the growth of human pituitary tumors [177]. Using nanoString-based technology, the authors identified a differential stem cell gene expression profile within human pituitary adenomas of all hormonal subtypes that indicated CD15 as a putative pituitary adenoma-initiating cell marker.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 99%